SPECIES COMPOSITION OF INTERTIDAL BIVALVES IN PRENDUAN BEACH, MADURA ISLAND - Nazihah, Fathimah Qonita; Ambarwati, Reni; Isnaningsih, Nur Rohmatin (BRIN Publishing (Penerbit BRIN), 2024)
Prenduan Beach on the southern coast of Sumenep Regency, Madura Island, is a habitat for various species of bivalves that may be used further. The objective of our research is to document and examine the bivalvia population in Prenduan Beach. Sampling was carried out using the 5 x 5 m quadrat plot method with a 1 x 1 m subplot at three stations with different substrates. The species diversity index (Shannon-Wiener) ranged from 1.15 to 1.36 and was classified as low. Relative abundance (RA) ranged from 0.63 to 60.63%. This study collected 159 bivalvia specimens from seven families and 11 distinct species. The two species with the highest relative abundance were Anadara antiquata (60.68%) and Solen sp. (15.72%). Both species have the potential to be used as a source of seafood.